Use of cyberspace resources for foreign language learning in higher education - Delplancq, Véronique (2018)
The learning of FL (foreign languages) for specific purposes, in HE (higher education), when we deal with students whose nuclear field of education has little or nothing to do with non - foreign languages, still gives rise to many problems, many questions and still needs to be readjusted. On the one hand, a good education in FL is essential to provide people with a wider general culture and represents a significant added value in terms of the students’ professional careers. Mastering foreign languages is becoming an increasingly important factor to support former students’ employability, to promote the competitiveness of companies and is vital to increase mobility. On the other hand, higher education institutions are currently experiencing a new phase in which they look for new teaching and learning methods, more in line with the evolution and the needs of modern society and of those to whom it provides its services. That way, and as far as FL are concerned, students need to be placed in real communicative contexts so they can truly improve their proficiency level. Interdisciplinarity allows for a complementary and cooperative work that will involve different skills and competencies and will provide a more consistent education. This article describes and analyses work experiences that were carried out with students attending the degree in Social Communication at the Escola Superior de Educação de Viseu (the Higher School of Education of Viseu , Portugal) in 2016/17 and 2017/18 as part of a Foreign Languages Curricular Unit whose objective was/is, among others, to develop a set of communicative skills that will prepare students to deal with situations they might have to solve in their future professional context. This will be achieved making use of the knowledge and know-how acquired in other Curricular Units and making the most of the potential offered by social networks and technologies. French and English were/are the two target languages, and were handled in the same circumstances, taking into account the achievement of the common objectives that had been designed for the students who the teachers involved were working with. Teachers acted mainly as tutors and helped implement a coaching environment. The goal was to grant all the students with a B2 level in situations related to specific professional tasks.